The Relationship between Single Parent Family Support and Adolescent Social Behavior - Dwi Putri, Hameisha; Natsir, MHD (Universitas Negeri Padang, 2025)
This study was motivated by the observed lack of single parent family support for adolescent social behavior, particularly in the emotional and informational aspects, and the poor communication established between single mothers and adolescents within single parent families. The objectives of this research were to determine: (1) the description of single parent family support; (2) the description of adolescent social behavior; and (3) the relationship between single parent family support and adolescent social behavior in Koto Baru Village, Air Hangat District, Kerinci Regency. The research employed a quantitative approach with a correlational design. The research population comprised adolescents aged 15–18 years from single parent families in Koto Baru Village, Air Hangat District, Kerinci Regency. The research sample was selected using a stratified random sampling technique. Data collection utilized a questionnaire as the main instrument. The data analysis techniques applied were the percentage formula and the Product Moment correlation formula. The research findings indicated that: (1) single parent family support was categorized as low; (2) adolescent social behavior was categorized as poor; and (3) there is a significant relationship between single parent family support and adolescent social behavior in Koto Baru Village, Air Hangat District, Kerinci Regency. Keywords: Family Support, Single Parent, Social Behavior, Adolescent